2019
DOI: 10.1039/c9lc00527g
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable microcontainers – towards real life applications of microfabricated systems for oral drug delivery

Abstract: We demonstrate the first complete study on fabrication of biodegradable microcontainers including their evaluation in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

10
0

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 40 publications
7
39
0
Order By: Relevance
“…While the ex vivo intestinal permeation studies showed the potential of unidirectional release for permeation enhancement across intestinal tissue, this effect was not observed in vivo. Fluorescent microscopic examination of the stomachs and small intestines of the rats after the in vivo study revealed that all MCs had undergone complete transit from ileum to caecum after 4 h, which is consistent with another recent study of biodegradable MCs [31]. Previous studies have shown SU-8 MCs embedded in the intestinal mucus in in situ intestinal perfusion studies [18].…”
Section: In Vivo Studiessupporting
confidence: 87%
“…While the ex vivo intestinal permeation studies showed the potential of unidirectional release for permeation enhancement across intestinal tissue, this effect was not observed in vivo. Fluorescent microscopic examination of the stomachs and small intestines of the rats after the in vivo study revealed that all MCs had undergone complete transit from ileum to caecum after 4 h, which is consistent with another recent study of biodegradable MCs [31]. Previous studies have shown SU-8 MCs embedded in the intestinal mucus in in situ intestinal perfusion studies [18].…”
Section: In Vivo Studiessupporting
confidence: 87%
“…Microcontainers in the biodegradable polymer PCL were fabricated by a hot punching process as previously described (Abid et al, 2019;Petersen et al, 2015). These microcontainers were fabricated on a water soluble PVA substrate containing 1,600 microcontainers.…”
Section: Fabrication Of Su-8 and Pcl Microcontainersmentioning
confidence: 99%
“…[31][32][33]. Recently, microcontainers were developed in poly-Ɛcaprolactone (PCL) in order to have a biodegradable oral drug delivery device in microscale [34]. In a pharmacokinetic study in rats, the PCL microcontainers revealed trends towards a higher AUC when compared to paracetamol in coated gelatin capsules (60 ± 33 and 39 ± 18 μg min ml −1 , respectively).…”
Section: Passive Microdevices For Oral Drug Delivery: Opportunities Amentioning
confidence: 99%